Legal Form, COVID and the Political: Notes Towards a Critique of the Corpus Iuris Pandemici - Mańko, Rafał (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The scholarly analysis and critique of law always take place under circumstances of scarcity of academic resources. At any given moment, the number of academic jurists mastering a given legal system and being capable of analysing and critiquing it at a professional scientific level is limited. The pandemic of COVID-19 only exacerbated this phenomenon, exposing the importance of making methodological and paradigmatic choices. What critical legal theory teaches us is that the choice of method and approach to the analysis and critique of legal materials is not politically neutral. Asking about the political goals and choices behind solutions adopted by legislators, ministers, civil servants, law enforcement officers, and judges, and about the actual interests impacted by their decisions is much more important and topical in these difficult times. A sociologically oriented critical legal theory can provide the necessary tools for such an analysis of the corpus iuris pandemici.